SEKALA NISKALA: Realitas Kehidupan Dalam Dimensi Rwa Bhineda - I Ketut Ardana (Pascasarjana Institut Seni Indonesia Surakarta, 2012)
Â The SekalaNiskalamusicwas inspired by the society social conflicts. It used cross culture concept asmusic applications thatcollaborate between the kwartets and gamelan luwang. It consists of three compositions are: Sekala,Niskala, and Ananda.Purpose of thismusic are: 1) gift knowledge to society obout the sekala niskala concept; 2) interpretations sekala niskalaworldin symbols, such as: tones andmelodys; 3) doing develop to traditionalmusicwith â€œnowdays creativityâ€; 4) result the newmusic. SekalaNiskalamusic can be useful for society as reflection the sekala niskala concept phenomenon in the publics live.SekalaNiskalamusic is considered newmusic that usingmusic character and semiotics approach.Keywords:music, rwa bhineda, sekala, niskala, ananda.